SHOX Variations in Idiopathic Short Stature in North India and a Review of Cases from Asian Countries - Priyanka Srivastava; Ankita Tyagi; Chitra Bamba; Anu Kumari; Harvinder Kaur; Saurabh Seth; Anupriya Kaur; Inusha Panigrahi; Devi Dayal; Subhodip Pramanik; Kausik Mandal (Galenos Yayincilik, 2024)
INTRODUCTION: Short stature homeobox (SHOX) haploinsufficiency underlies idiopathic short stature (ISS) and Leri-Weill dyschondrosteosis. The worldwide prevalence of SHOX variations in ISS varies from 2.5% to 15.0%. The aim of this study was to assess the implication of SHOX variation in ISS in North Indians and compare this with other cases of SHOX variations from Asian population. METHODS: SHOX gene analysis was carried out by multiplex ligation-dependent probe amplification followed by Sanger sequencing in 54 patients with variable phenotypes. Comparison with other reports in a meta-analysis comprising the current study and 11 previous studies (n=979) was performed. RESULTS: SHOX analysis resulted in 12.9% positivity (7.4% deletions and 5.5% duplications). SHOX association was seen significantly related to gender, with predominance in females (p=0.047). Short arms and forearms were the only significantly associated trait seen in 51.9% of children. The overall prevalence of SHOX variation was 15.2% in Asians with ISS. No significant difference was found in geographical region-specific analysis. DISCUSSION AND CONCLUSION: This study summarises findings from the last decade and provides an updated picture of the prevalence of SHOX variations in Asians, emphasizing their potential as therapeutic targets in ISS patients. Further high quality, large investigations including functional validation is warranted to validate this association.